Who Is Benefiting from Fertilizer Subsidies in Indonesia? - Gomez Osorio, Camilo; Abriningrum, Dwi Endah; Blanco Armas, Enrique; Firdaus, Muhammad (2012)
Using the Agricultural Census 2003 and the Rice Household Survey 2008 for Indonesia, this paper analyzes the distribution of benefits from fertilizer subsidies and their impact on rice production. The findings suggest that most farmers benefit from fertilizer subsidies; however, the 40 percent largest farmers capture up to 60 percent of the subsidy. The regressive nature of the fertilizer subsidies is in line with research carried out in other countries, the result of larger farms using a larger volume of fertilizer. This paper confirms that fertilizer used in adequate quantities has a positive and significant impact on rice yields, but it also provides evidence that over-using fertilizer has an adverse impact on yields (an inverted U-curve relationship).